The connectivity and security of the sensors combined with the architecture ensure a reliable and functional IoT. - Christos P. Beretas (Peneliti Teknologi Teknik Indonesia, 2023)
In recent years, the rapid growth in electronics, computing and the growing needs of people for communication, automation, electronic transactions, and electronic conveniences has helped develop new technologies that have evolved in our lives to make it easier by simplifying communication with people around us and simplifying various online services. IoT is a trend that has begun with enthusiasm, is currently underway and will continue to evolve over the years. In developed countries in the world, especially in the USA and Europe, there are thousands of online devices that perform specific tasks daily, such as electrical water pumps, statistical data collection, network control, vehicle guidance, food supply, motion sensors, patient monitoring, etc There are so many IoT manufacturers that each manufacturer applies their own security way, or they do not even apply security, considering Android itself is capable of defining and automatically protect the IoT. The scientific community has put the emphasis on upgrading protocols and services, providing more capabilities but significantly ignoring the security of the infrastructure that will be installed an IoT.